2017
DOI: 10.1101/101832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide phenotypic analysis of growth, cell morphogenesis and cell cycle events in Escherichia coli.

Abstract: Cell size, cell growth and the cell cycle are necessarily intertwined to achieve robust bacterial replication. However, a comprehensive and integrated view of these fundamental processes is lacking. Here, we describe an image-based quantitative screen over the single-gene knockout collection of Escherichia coli, which led to the identification of many new genes involved in cell morphogenesis, population growth, nucleoid (bulk chromosome) dynamics and cell division. Functional analyses, together with high-dimen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 93 publications
5
23
0
Order By: Relevance
“…intermediates is independent of und-P sequestration or σ E and Cpx stress response pathways Recently, it has been reported that the build-up of ECA "dead-end" intermediates can lead to sequestration of und-P, the common precursor for many sugar polymers in the cell envelope including peptidoglycan; this gives rise to shape defects such as filamentation and swelling Campos et al, 2018). In our strains that lack colanic acids, we also observe similar shape defects.…”
Section: Suppression Of Om Permeability Defects In Tol-pal Strains VIsupporting
confidence: 79%
“…intermediates is independent of und-P sequestration or σ E and Cpx stress response pathways Recently, it has been reported that the build-up of ECA "dead-end" intermediates can lead to sequestration of und-P, the common precursor for many sugar polymers in the cell envelope including peptidoglycan; this gives rise to shape defects such as filamentation and swelling Campos et al, 2018). In our strains that lack colanic acids, we also observe similar shape defects.…”
Section: Suppression Of Om Permeability Defects In Tol-pal Strains VIsupporting
confidence: 79%
“…Thus, new methods (e.g., high-throughput microscopy, flow cytometry, etc.) have been used to measure morphology when screening or selecting for mutants (13)(14)(15)(16)(17)(18), resulting in the discovery of new factors connected to cell division and morphogenesis. However, many of the morphological phenotypes discovered in these reports have no mechanistic explanation, and some lack functional annotation altogether.…”
mentioning
confidence: 99%
“…Modest defects in cell division are well known to increase bacterial cell size—particularly length—without impacting growth rate [4,7,50,51,53], while defects in transcription severely curtail growth but have little detectable impact on morphology [6]. Most importantly, an exhaustive phenotypic analysis of the entirety of non-essential genes in E. coli by the Jacobs-Wagner group, failed to identify any evidence supporting a direct connection between growth rate and size [54].…”
Section: Discussionmentioning
confidence: 99%